GREEN TECHNOLOGY APPLICATIONS: THE AWARENESS OF AIR VENTILATOR EFFECT TOWARDS RESIDENTIAL INDOOR AIR QUALITY (Journal of Technology and Operations Management, 2012)
This study explores the usage of air ventilator as one of the green technology applications at the residential areas. The stale air never goes out through the openings and entrances through which the wind enters the housing, thus it known as indoor pollutant emissions. Nowadays, a lot of residential health problems related to respiratory diseases are amplified for examples asthma, bronchitis, hay fever, and emphysema. Most all of these diseases are coming from the residential stale air. Thus, this study intends to explore the residential awareness of maintaining a good indoor air quality in their houses, respiratory problematic and the impact of air ventilators. Qualitative approach with convenience sampling becomes backbone of the study. Data are gathered through semi-structured interviews with thirty respondents and some pictures are also taken. Each interview session is lasting not more than 1 Â½ hours and recorded with a digital recorder. The transcriptions of interviews were mailed to them right after three days. Among the significant results from the study are; 76% of respondents claimed the prices of the device are inexpensive, and 73% claimed their family members of asthma attacks are reduced as well as the allergic symptoms. The study is planned to further up to include major cities to see it implications.